An auction story: How simple bids struggle with uncertainty - Jörn C. Richstein; Casimir Lorenz; Karsten Neuhoff (Energy Economics, 2020)
Short-term electricity markets are key to an efficient production by generation units. We develop a two-period model to assess different bidding formats to determine for each bidding format the optimal bidding strategy of competitive generators facing price-uncertainty. We compare the results for simple bidding, block bidding and multi-part bidding. We find that even under optimal simple and block bidding, generators face the risk of ex-post suboptimal solutions, whereas in multi-part bidding these do not occur. This points to efficiency gains of multi-part bidding in the presence of uncertainty in electricity markets.
Keywords: D44; D47; Q48; L94; 330; Market design; Electricity markets; Bidding formats; Auctions